A mixed-methods investigation to understand and improve the scaled-up infection prevention and control in primary care health facilities during the Ebola virus disease epidemic in Sierra Leone - Lara Shiu-yi Ho; Ruwan Ratnayake; Rashid Ansumana; Hannah Brown (BMC, 2021)
Abstract Background The 2014-2015 Ebola epidemic in West Africa became a humanitarian crisis that exposed significant gaps in infection prevention and control (IPC) capacity in primary care facilities in Sierra Leone. Operational partners recognized the national gap and rapidly scaled-up an IPC training and infrastructure package. This prompted us to carry out a mixed-methods research study which aimed to evaluate adherence to IPC practices and understand how to improve IPC at the primary care level, where most cases of Ebola were initially presenting. The study was carried out during the national peak of the epidemic. Discussion We successfully carried out a rapid response research study that produced several expected and unexpected findings that were used to guide IPC measures during the epidemic. Although many research challenges were similar to those found when conducting research in low-resource settings, the presence of Ebola added risks to safety and security of data collectors, as well as a need to balance research activities with the imperative of response to a humanitarian crisis. A participatory approach that attempted to unify levels of the response from community upwards helped overcome the risk of lack of trust in an environment where Ebola had damaged relations between communities and the health system. Conclusion In the context of a national epidemic, research needs to be focused, appropriately resourced, and responsive to needs. The partnership between local academics and a humanitarian organization helped facilitate access to study sites and approvals that allowed the research to be carried out quickly and safely, and for findings to be shared in response forums with the best chance of being taken up in real-time.